PENGARUH PEMBERIAN EKSTRAK KULIT PISANG KEPOK KUNING (Musa balbisiana) TERHADAP ASUPAN MAKAN DAN BERAT BADAN TIKUS WISTAR (Rattus norvegicus) JANTAN - Wiwiek Fatchurohmah; Andreanyta Meliala (Scripta Biologica, 2017)
A positive energy imbalance results in overweight and obesity. Overweight and obesity are the major risk factors for many diseases, including diabetes, cardiovascular diseases, and mental health. Animal studies suggested that serotonin involves in food intake control. The Banana peel is a potential natural source of serotonin precursor; furthermore, it may influence food intake. This study aimed to determine the effect of banana peel extract on food intake and body weight gain in male Wistar rats. Twenty-four male Wistar rats (8-10 weeks old), were divided into four groups for feeding treatment. All four group were; the control group (C), the banana peel extract dosage of 4 g/kg BW group (T1), the banana peel extract dosage of 8 g/kg BW (T2), and the banana peel extract dosage of 16 g/kg BW (T3). The food intakes were measured daily, while rats body weights were recorded at the beginning and the end of the three days experimental periods. The study found the rats in the T1 group (8.80 ± 2.63) showed no significant difference in food intake compared to C group (10.68 ± 1.89), T2 group (6.65 ± 3.12), and T3 group (5.42 ± 1.59). Rats in the T2 group (p = 0.038) and T3 group (p = 0.005) showed lower food intake significantly compared to control group. After three days of treatment, the T3 group showed a significant decrease in body weight compared to control group (p = 0.008). This study concluded, the administration of banana peel extract dosage of 8 g/kg BW and 16 g/kg BW suppressed food intake, while the dosage of 16 g/kg BW reduced the body weight in male Wistar rats.